Microsoft Entra ID for JavaScript Developers. - Malik, Sahil (linkedin.com, 2024)
This course shows JavaScript developers how to leverage Entra ID for authentication services for applications, call existing APIs such as Microsoft Graph, and author Node.js APIs.